Subjective Preferences and Discomfort Ratings of Backrest and Seat Pan Adjustments at Various Speeds - Jingdong Li; Yu Huang (Applied Sciences, 2021)
Power seats (i.e., electrically adjustable seats that can be designed to move in several ways) have become increasingly common in airplanes, vehicles, and offices. Many studies have investigated the effects of seat attitude parameters, for example, the inclined angles of a backrest, on discomfort during the adjustment process. However, few studies have considered discomfort under different speeds during the adjustment process. In this study, we investigated discomfort with three speeds (i.e., “fast”, “median”, and “slow” corresponding to three durations of 15, 20, and 25 s, respectively) and two adjustments of a power seat, i.e., incline angle adjustment of the backrest and fore-and-aft position adjustment of the seat pan. We also investigated the effects of different physiological parameters on subjects’ discomfort. Twenty-four subjects (12 males and 12 females) completed a questionnaire to indicate their adjustment condition preferences, to rate their overall discomfort during the adjustment processes on a category-ratio scale, and to rate their local body discomfort. The majority of subjects preferred the fast speed adjustment condition and the trend was that a lower backrest adjustment speed increased discomfort during the process. The dominant local discomfort was in the upper and lower back regions during the backrest adjustment, whereas there was no obvious dominant local discomfort during the seat pan adjustment. The physiological parameters also had significant correlations with discomfort in some adjustment movements, for example, the discomfort was negatively correlated with height during the backrest adjustment.